Analysis of snap-through behavior of bistable buckled beam under end-moment static actuation. (June 2022) - Pan, Diankun; Shen, Yuping; Huang, Chenghang; Wu, Zhangming
Abstract: Bistable buckled beams are one of the most prevalent types of bistable mechanisms due to their simple structural forms, which have attracted significant research attention and wide applications in switches, actuators, and energy harvesters, etc. In general, a mid-span or off-center force is often applied as the external input to actuate the snap-through behavior of bistable buckled beams. Apart from the force actuation, the method of moment actuation for bistable buckled beams is rarely used and studied. Compared with force actuation, moment actuation has certain advantages when the driving motion is out-of-plane rotation. In this work, the first purpose is to analyze the snap-through behavior of the simply supported bistable buckled beam subjected to a concentrated moment applied at one end of the beam. An analytical model based on the energy method is developed to analyze the snap-through behavior of bistable buckled beams, in particular for predicting the moment–angle curves. Moreover, an experimental setup that consists of a torque sensor and a motor is established to analyze the moment–angle responses for bistable beams and verify the analytical model. The finite element model is also established to obtain numerical results to approve the analytical model, which can provide accurate prediction for bistable buckled beams under force actuation. However, compared with FEA results, the analytical model leads to a certain amount of difference in predicting the moment–angle curves of bistable beams under the moment actuation. Therefore, the reasons causing this difference are investigated, and the analytical model is further improved by introducing polynomials into the shape function to obtain more accurate results, which are then well-matched with FEA and experimental results. At last, a parametric analysis is carried out to further study the influence of geometric parameters and pre-compression on the moment–angle curves of snap-through behavior of bistable beams under this end-moment actuation method. Highlights: The snap-through behavior of bistable buckled beam subjected to a concentrated moment actuation is investigated. An analytical model is developed to predict the moment–angle curves representing the snap-through process. A finite element model is performed and an experimental setup is established to verify the analytical model. A parametric analysis is carried out to study the influence of geometry and pre-compression on the moment–angle curves.